2020
DOI: 10.31234/osf.io/y5grn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conspiracy theories and their societal effects during the COVID-19 pandemic

Abstract: Conspiracy theories offer unvalidated explanations for important political and societal events and thus are likely to develop around a crisis, such as the Corona pandemic. Research has shown that a general tendency to believe in conspiracy theories—a so-called conspiracy mentality—comes with negative societal consequences, such as decreased social engagement and less trust in authorities. However, this has not been tested for concrete conspiracy theories like the ones around the Corona pandemic. Social engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 11 publications
5
40
0
1
Order By: Relevance
“…Adding to the robustness of the findings, another study conducted within the German context (reported in the Supplemental Material) closely replicated this general pattern. This seems noteworthy as another data set from the German context failed to find strong relations between conspiracy endorsement and hygiene measures (Pummerer & Sassenberg, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Adding to the robustness of the findings, another study conducted within the German context (reported in the Supplemental Material) closely replicated this general pattern. This seems noteworthy as another data set from the German context failed to find strong relations between conspiracy endorsement and hygiene measures (Pummerer & Sassenberg, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Pseudoscientific health practice may be adopted instead of scientifically supported safeguarding behaviours 5,6,15,22,103,106 , which often promote anti-vaccination attitudes, which might further explain the relation between conspiracy beliefs and reduced vaccinations intentions 13,61,90 .…”
Section: Discussionmentioning
confidence: 99%
“…Distrust in the government, the military, doctors, scientists, the World Health Organization (WHO), the United Nations, and the European Union (EU) were associated with belief in COVID-19 conspiracy theories in England 5 and in part in Romania82 . Distrust in government officials further mediated the relationship of (political) COVID-19 and generic conspiracy beliefs with reduced adherence to guidelines in Croatia7 and Germany86,90 . Moreover, for citizens in the United States, belief in COVID conspiracy theories was associated with more trust in the country's government15 and President Trump…”
mentioning
confidence: 99%
“…Informationally, the COVID-19 pandemic has led to an "infodemic" that is, the deliberate and massive circulation of "wrong information to undermine the public health response" (WHO, 2020c). Given the historical abundance of conspiracy theories about vaccines, it is unsurprising that COVID-19 vaccination has also been a key target of misinformation (e.g., Imhoff & Lamberty, 2020;Pummerer et al, 2020), something that may have led to increased vaccine hesitancy during the pandemic . Added to this informational challenge is an equally potent motivational challenge-that is, motivating vaccination even among those not directly at risk of severe illness from .…”
Section: Introductionmentioning
confidence: 99%